Soil science for bean production - National Bean Programme (National Bean Programme, 1990)
In trials carried out to evaluate the effects of applying 0, 40, 80, and 120 kg N/ha on N uptake by intercropped maize and bean, the N content of 4-wk-old bean plants did not differ significantly among N fertilizer levels and cropping systems. However, there were significant differences among bean var., the highest N absorption rates being observed in climbing bean var. Kanzama. Bean seed yields increased with higher levels of N. In another trial carried out on the effects of both inoculation and 0, 25, and 50 kg P/ha on biological N fixation in 3 bean var. (Nasaka, P402, and 13-3), effective nodulation was highest when 50 kg P was applied per ha and Rhizobium MG 366 was inoculated. Applying P to inoculated bean seed can significantly increase nodulation and consequently N fixation rate. There were no significant differences in seed yields among treatments; however, P application increased av. seed yields. The best response to inoculation was obtained with P402 (1200 kg seed/ha with 25 kg P). (CIAT)